Menganalisis Penyebab Korupsi di Berbagai Profesi pada Era Negara Indonesia Yang Menjadikan Pancasila Sebagai Dasar Negara - Aprilla Haryanti; Nazwa Aura Rahmadhani; Mutia Arifah; Ilham Hudi; Hasiela Nurfajrina Seprizal; Ray Febisya Thawil Wahid (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Corruption is one of the biggest problems that hinders Indonesia's progress, even though this country uses Pancasila as the basis of the state. Pancasila should be a moral guideline in every aspect of national and state life, including in preventing corruption. This study aims to analyze the causes of corruption in Indonesia in various professions, as well as to examine the relationship between the application of Pancasila values and corrupt practices in this country. The study uses a library method by analyzing 47 articles and journals from 2020-2024. The research findings show that the main causes of corruption in Indonesia include weak law enforcement, a deep-rooted culture of corruption, inability to manage power, and socio-economic disparities.